Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Les femmes dans les associations du secteur environnement - Flahault, Erika (Femmes et villes, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; environnement; europe; france; militance; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail

Femmes et pouvoirs : à la conquête des territoires - Institut de recherches et d'études féministes (FéminÉtudes, 2004)
Cette publication aborde les conquêtes passées et en cours pour l’accès au pouvoir des femmes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-9-no-1-2004-femmes-et-pouvoirs/
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; droits des femmes*; espace public; féminétudes; histoire et politique; militance; pouvoir; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Publisher: Taylor & Francis
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Organizational "emotion work" through consciousness-raising: An analysis of a feminist organization - Reger, Jo (Qualitative Sociology, 2004)
In this article I explore how organizational processes link to certain emotional responses, as a way of investigating more fully the role emotions play in social movements. Through the construction of a case study of a feminist group, the New York City chapter of the National Organization for Women (NYC NOW), I analyze how certain emotions, such as anger, alienation, hopelessness and frustration, are redefined within an organizational context. I find that consciousness-raising serves as the organizational process that helps transform personal emotions into a collectively defined sense of injustice. This transformation has the potential of creating actors dedicated to chapter activism.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; care; discipline; militance; mouvements féministes; new york; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis; étude qualitative